MENINGKATKAN AKSES KEADILAN BAGI MASYARAKAT MARGINAL MELALUI LAYANAN HUKUM GRATIS - Arif Fikri; Sawaluddin Siregar; Agustina Damanik (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2025)
The gap in access to legal justice remains a reality faced by marginalized communities in various regions, particularly those who are poor, less educated, and live in remote areas. This article examines the implementation of free legal services as a form of community service in an effort to improve access to substantive justice. Activities are carried out through a participatory approach involving academics, students, and legal practitioners, with a focus on legal education, consultations on civil and minor criminal cases, and administrative assistance. The results of the activities indicate that free legal services not only play a role in resolving legal problems directly but also increase community awareness and legal empowerment. These findings emphasize the importance of inclusive and sustainable community-based legal aid institutions to strengthen the democratization of access to the justice system.